1995
DOI: 10.5935/0305-7518.19950026
|View full text |Cite
|
Sign up to set email alerts
|

Tibialis posterior transfer in the correction of footdrop due to leprosy

Abstract: SummaryIn the correction of fo otdrop due to leprosy neuritis the tibialis posterior muscle is re-routed and used to provide dorsiflexion of the fo ot. This study of tibialis posterior transfer was carried out to compare the results of the circumtibial and interosseous routes. There is no significant difference in the range of motion between either route though the range of the interosseous route is more functional (better dorsiflexion). The interosseous route is prefer able as this results in a significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…Others used too varying scoring systems to evaluate gait, some without defining the result clearly. 9,35,39 Active dorsiflexion to neutral or beyond was achieved in 9 of the 13 transfers with a median of 0 degrees, which is comparable to the literature regarding other techniques (50% to 95% reaching at least neutral, with an average of about -3.3 to 10 degrees, Tables 4 and 5). The median active plantarflexion and range of motion (both 40 degrees) also are similar to the results in the literature regarding other techniques (9 to 43 degrees and 17 to 40 degrees respectively, Tables 4 and 5).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Others used too varying scoring systems to evaluate gait, some without defining the result clearly. 9,35,39 Active dorsiflexion to neutral or beyond was achieved in 9 of the 13 transfers with a median of 0 degrees, which is comparable to the literature regarding other techniques (50% to 95% reaching at least neutral, with an average of about -3.3 to 10 degrees, Tables 4 and 5). The median active plantarflexion and range of motion (both 40 degrees) also are similar to the results in the literature regarding other techniques (9 to 43 degrees and 17 to 40 degrees respectively, Tables 4 and 5).…”
Section: Discussionsupporting
confidence: 78%
“…Others used too varying scoring systems to evaluate gait, some without defining the result clearly. 9,35,39…”
Section: Discussionmentioning
confidence: 99%
“…19 In contrast, Soares's study shows that both methods yield above-neutral dorsiflexion in 80% of the patients, and from the viewpoint of dorsiflexion both methods are equally successful. 18 In our series, we did not face the problems previously described for the circumtibial route, such as foot inversion or cosmetic problems like the visibility of the tendon in the subcutaneous tunnel. In addition, the Andersen tendon carrier, owing to its blunt edge and curved body, facilitated easy transfer of the tendon anteriorly.…”
Section: Discussionmentioning
confidence: 90%
“…Soares used tendon-tendon insertion and reported that between the time of suture and discharge from the hospital, there would be a 10-degree decrease in dorsiflexion, and a further 5-to 10-degree decrease during follow-up. 18 Therefore he suggested suturing the tendons while the ankle is kept at 20 degrees of dorsiflexion to compensate for this decrease. During transfer, we keep the ankle at 20 to 30 degrees of dorsiflexion and the TP tendon tight.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, tendon transfer has been shown to improve patient satisfaction by increasing mobility and walking independence. In the treatment of foot drop, tendon transfer over the interosseous membrane and tendon fixation to bone have been the preferred techniques in recent years [8][9][10]. In our case, we used combined tendon-totendon and tendon-to-bone fixation, preferring the circumferential route and the superficial retinacular passage.…”
Section: Introductionmentioning
confidence: 97%